The Carbon Isotope Ratio of Breath Is Elevated by Short and Long-Term Added Sugar and Animal Protein Intake in a Controlled Feeding Study. (7th June 2021) - O'Brien, Diane; Tasevska, Natasha; Sagi-Kiss, Virag; Palma-Duran, Susana A; Barrett, Brian; Commins, John; Rivera, Patricia; Johnston, Carol; Midthune, Douglas; Kipnis, Victor
Abstract: Objectives: Objective biomarkers would help to clarify relationships between added sugar (AS) intake and chronic disease. A recent study identified the breath carbon isotope ratio (CIR) as a potential short-term AS biomarker. To further evaluate the biomarker potential of the breath CIR, we evaluate the effects of both short and longer-term intakes of AS in the context of normal dietary intake patterns, and also evaluate animal protein (AP), another dietary factor known to influence CIR. Methods: We conducted a 15-d controlled feeding study of 100 adults (age 18–70, 55% women) in Phoenix, AZ. Participants were provided individualized diets that approximated habitual food intakes and recorded the time that all foods were consumed throughout each day. Three breath samples were collected on each of 3 nonconsecutive, randomly selected study days: one fasting sample, one "morning" sample (collected 10:00–14:00) and one "evening" sample (collected 14:00–20:00). We used a linear mixed model to evaluate the effects of AS and AP intake in each of 8 hours preceding collection of the breath sample ( t 1  = 0–1 hour prior, t 2  = 1–2 hours prior, etc.). Besides daily intake, models also included 15-d mean AS and AP intake, as well as sex, age and BMI. Coefficients are presented as (β (SE), P ). Results: Mean (±SD) intakes of AS and AP in our study were 67 ± 34 and 73 ± 30 g/d, respectively. The breath CIR was increased by AS consumed 1–4 hours prior to sample collection (β t 2  = 0.014 (0.005), P  = 0.0025; β t 3  = 0.0094 (0.004), P  = 0.02; β t 4  = 0.012 (0.005), P  = 0.02) and AP consumed 3–6 hours prior to sample collection (β t 4  = 0.012 (0.005), P  = 0.03; β t 5  = 0.0092 (0.004), P  = 0.03; β t 6  = 0.010 (0.006), P  = 0.09). In addition, the breath CIR increased with higher 15-d intakes of both AS and AP (βAS  = 0.012 (0.003), P < 0.0001 and βAP  = 0.014 (0.004), P  = 0.0003, respectively). Conclusions: Both short-term and longer-term intakes of AS and AP increased the breath CIR. Short-term AS intake had a more rapid effect on the breath CIR than short-term AP intake, although effects were of similar size. Furthermore, the size of short-term effects were similar to the size of long-term effects. Thus, breath CIR is influenced by both short and long-term intakes of AS and AP and could have potential for evaluating dietary patterns. Funding Sources: This work was funded by NIH U01 CA197902.